Perancangan Sederhana Menggunakan Bahasa Pemrograman Visual Basic. Net 2010 Dengan Database Mysql - Sabrina Rahmahdani; Yahfizham (CV. ITTC INDONESIA, 2024)
The development of information systems is too affected by advances in science and technology. A system is needed in order to provide all data accurately and precisely. The system uses Visual Basic Net 2010 programming language with MySQL database. This article is expected to facilitate sales in managing data to be more accurate. By using the method of literature study, design and applied research (Applied research) which makes it easy to make this article. Based on the results of the design that the author made with the Visual Basic Net 2010 programming language and the MYSQL database, where the design that has been done is more effective and efficient, this design includes data processing features that are useful for minimizing data entry time.